2005
DOI: 10.1007/s00420-004-0541-2
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic field exposure and arrythmic risk: evaluation in railway drivers

Abstract: Recent studies suggest that professional exposure to Extremely Low Frequency-Electro Magnetic Field (ELF-EMF) can increase the risk of sudden cardiac death. Aim of our work was to find predictive parameters of arrhythmic risk in a population of 28 railways drivers exposed to ELF-EMF. Our findings were that the exposure did not reduce HRV and did not increase the risk of arrhythmias.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Exposures to chemicals or electric shocks, which often occur in other occupational settings (for example in electric utility workers or welders) are rare. Previous studies of railway workers have focussed on cancer risks [4][5][6][7][8] , chromosomal aberrations [9] and cardiovascular disease [10,11] . Only 1 such study has so far investigated the risk of neurodegenerative diseases in railway employees [12] .…”
mentioning
confidence: 99%
“…Exposures to chemicals or electric shocks, which often occur in other occupational settings (for example in electric utility workers or welders) are rare. Previous studies of railway workers have focussed on cancer risks [4][5][6][7][8] , chromosomal aberrations [9] and cardiovascular disease [10,11] . Only 1 such study has so far investigated the risk of neurodegenerative diseases in railway employees [12] .…”
mentioning
confidence: 99%
“…As Table 2 suggests, magnetic flux density at the times of acceleration and breaking showed a significant difference in AC (P < 0.001) and ACi trains (P < 0.002). In the same study as well as in the research by Farag et al (2003) (10), it was revealed that the magnetic flux density also increases with increasing speed. The speed difference is also observed in in-city and intercity trains of Tehran City.…”
Section: Discussionmentioning
confidence: 49%
“…A number of studies have warned about the health effects of exposure to MF in rail transit. The most commonly reported of which include a 3-fold increased risk for chronic lymphocytic leukemia in engine drivers (7), double incidence rate of chronic and acute lymphocytic leukemia in engine drivers and conductors compared to the average Swedish male population (8), altering the urinary 6-hydroxymelatonin sulfate excretion (9), increased risk of sudden cardiac death (10), and cardiovascular mortality (11). Exposure to MF induced by electrified public transport has been the center of concern in different countries such as Malaysia (12), Russia (13,14), Italy (15), and Australia (4).…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned by the authors, this could lead to criticism that "actual levels of EMF exposure in some of these occupational groups are somewhat uncertain" (Ahlbom et al 2004). Similarly, the study by Santangelo et al (2005) consisted of only 28 railway drivers; the authors also suggested that confounding factors such as stress and the timing of measurements taken for the referent group (within 6-20 h after exposure) could have played a role in the study outcome.…”
Section: Epidemiological Studiesmentioning
confidence: 89%
“…Despite these changes, no eVect was found on mean HR or HRV. Santangelo et al (2005) studied arrhythmic risk in a small population of 28 railway drivers exposed to ELF-EMF; they found that not only did exposure not increase the risk of arrhythmias, but also it had no apparent aVect on HRV. Most recently, Bortkiewicz et al studied neurovegetative disturbances in 63 switchyard workers exposed to 50 Hz EMFs.…”
Section: Epidemiological Studiesmentioning
confidence: 99%